Tinjauan Literatur tentang Cloud Computing dan Artificial Intelligence (AI) Potensi dan Tantangan - Ganes Wisnu Cahya Bagaskara,; Nono Heryana, (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2024)
Artificial intelligence (AI) has become a key element in industrial development and plays a crucial role in driving the integration of emerging technologies such as graphic processing units, Internet of Things, blockchain, and cloud computing in the new era of big data and Industry 4.0. The integration of cloud computing and artificial intelligence (AI) holds great potential across various fields. By combining the flexible and scalable nature of cloud computing with the complex data analysis capabilities of artificial intelligence, this technology can provide innovative solutions in data processing, decision-making, and process automation. However, there are challenges to be addressed in integrating these two technologies, and the use of cloud computing and AI also presents potential negative implications. Further research is needed to optimize the benefits offered by this integration while addressing associated constraints and risks.
Keywords: Cloud Computing, Artificial Intelegance, Machince Learning.